Neuroimaging characteristics of patients with focal hand dystonia. - Hinkley, Leighton B.N. (J Hand Ther, 2009)
Advances in structural and functional imaging have provided both scientists and clinicians with information about the neural mechanisms underlying focal hand dystonia (FHd), a motor disorder associated with aberrant posturing and patterns muscle contraction specific to movements of the hand. Consistent with the hypothesis that focal hand dystonia is the result of reorganization in cortical fields, studies in neuroimaging have confirmed alterations in the topography and response properties of somatosensory and motor areas of the brain. Non-invasive stimulation of these regions also demonstrates that focal hand dystonia may be due to reductions in inhibition between competing sensory and motor representations. Compromises in neuroanatomical structure, such as white-matter density and gray matter volume, have also been identified through neuroimaging methods. These advances in neuroimaging have provided clinicians with an expanded understanding of the changes in the brain that contribute to focal hand dystonia. These findings should provide a foundation for the development of retraining paradigms focused on reversing overlapping sensory representations and interactions between brain regions in patients with hand dystonia. Continued collaborations between health professionals that treat focal dystonia and research scientists that examine the brain using neuroimaging tools are imperative for answering difficult questions about patients with specific movement disorders.